(untitled) (Mustansiria Dental Journal, 2018)
During two years period from 2009-2010 cases with oral lesions and oral diseases were recorded and analyzed, based on clinical, radiographic and biopsy examinations. The oral diseases were divided into 8 groups ,including 110 cases oral lesion, other oral diseases were trailing well behind ,followed by soft tissue swelling 51 cases, ,congenital anomalies48 cases ,bone diseases 45 cases ,salivary gland diseases 31,other conditions 18cases , and neuralgia 14 cases.